1989
DOI: 10.1007/bf00386483
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and specificity of IgE antibodies to isocyanates in occupationally exposed workers

Abstract: The levels of IgE antibodies specific for toluene-diisocyanate (TDI), diphenylmethane-diisocyanate (MDI) and hexamethylene-diisocyanate (HDI) were determined in eight workers with an unequivocal history of professional asthma, all having been exposed to isocyanates in the working atmosphere. Five workers were examined at the clinical onset of asthma. They had serum IgE antibodies specific for TDI, MDI and HDI, and depressed pulmonary ventilation parameters. In contrast, three workers, who had only a mild bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Tee et al (1998) also reported that subtracting HSA binding from conjugate binding improved test performance in discriminating among OA cases and noncases. For classification of positive responses, a RAST ratio of 2 or higher has been used most often (Keskinen et al, 1988;Cvitanovic et al, 1989;Park and Nahm, 1996, Deschamps et al, 1998, Nosko et al, 1998, but a ratio of 3+ (Wass and Belin, 1989) has also been employed, as well as a RAST ratio greater than the highest of 22 nonexposed controls (Welinder et al, 1988). Few studies have examined the consequences of using different definitions for a positive response on test performance.…”
Section: Defining a Positive Test Resultsmentioning
confidence: 97%
“…Tee et al (1998) also reported that subtracting HSA binding from conjugate binding improved test performance in discriminating among OA cases and noncases. For classification of positive responses, a RAST ratio of 2 or higher has been used most often (Keskinen et al, 1988;Cvitanovic et al, 1989;Park and Nahm, 1996, Deschamps et al, 1998, Nosko et al, 1998, but a ratio of 3+ (Wass and Belin, 1989) has also been employed, as well as a RAST ratio greater than the highest of 22 nonexposed controls (Welinder et al, 1988). Few studies have examined the consequences of using different definitions for a positive response on test performance.…”
Section: Defining a Positive Test Resultsmentioning
confidence: 97%
“…The argument that immunologic mechanisms lie behind isocyanate-induced bronchoconstriction is supported by the detection of serum-specific IgE [2, 4, 6, 7, 8]and IgG [2, 9]antibodies to isocyanates. However, the significance of specific IgE and IgG antibodies in the pathogenesis of isocyanate-induced asthma remains unclear, since most patients have no evidences of antibodies to isocyanates [2, 4, 6, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 90%
“…However, the significance of specific IgE and IgG antibodies in the pathogenesis of isocyanate-induced asthma remains unclear, since most patients have no evidences of antibodies to isocyanates [2, 4, 6, 7, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…IgE antibodies are classically associated with immediate hypersensitivity reactions and are associated with acute exposures to isocyanates and changes in pulmonary function. 9,10 IgE and IgG titers to isocyanates have been associated with severe disease. 11 In subjects with positive inhalation challenges to hexamethylene diisocyanate (HDI) and diphenylmethane diisocyanate (MDI), IgG titers were more closely associated with disease than IgE titers.…”
Section: Immunologic Testing (Igg and Ige Titer) And The Evaluatiomentioning
confidence: 99%
“…Follow-up visits were conducted March 8-9, 1989; August 9-10, 1989; January 23-25, 1990; February 6-7, 1990; and May [9][10]1990. Interim reports were distributed on July 14, 1989, and February 2, 1990, and participants were notified of their own test results on December 13, 1989; March 13, 1990; and July 14,1990.…”
Section: Introductionmentioning
confidence: 99%